2016
DOI: 10.1292/jvms.15-0626
|View full text |Cite
|
Sign up to set email alerts
|

Influence of transfusion of lymphokine-activated T killer cells on inflammatory responses in dogs after laparotomy

Abstract: The influence of transfusion of lymphokine-activated T killer cells (T-LAK) on inflammatory responses was examined in dogs after laparotomy. Plasma C-reactive protein (CRP) level, cell numbers of peripheral blood lymphocytes (PBLs) and T lymphocyte subsets (CD3+, CD4+ and CD8+) and mRNA expression levels of cytokines including interleukin (IL)-2, IL-12, IL-4, IL-10 and transforming growth factor (TGF)-β in peripheral blood mononuclear cells (PBMCs) were measured in dogs with (T-LAK group) or without (control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
3
4
0
Order By: Relevance
“…CD8+ cells were predominant among the activated lymphocytes, and a significantly increased number of IFN‐γ‐producing cells were observed. These results are consistent with those obtained in previous studies …”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…CD8+ cells were predominant among the activated lymphocytes, and a significantly increased number of IFN‐γ‐producing cells were observed. These results are consistent with those obtained in previous studies …”
Section: Discussionsupporting
confidence: 94%
“…The isolation, culture and expansion of immune cells were performed with modifications according to procedures reported in previous studies . Two weeks before starting EBIC therapy, 10 mL of the dog's own peripheral blood was collected in vacuum tubes coated with heparin (BD Vacutainer ® , Becton Dickinson; Franklin Lakes, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interleukin-2 (IL-2) was used as a mitogen for lymphocyte activation. The isolation, culture, and expansion procedures for immune cells were obtained and modified from previous studies (7,8). The phenotypes of cells before and after processing were analyzed by flow cytometry, and the outcomes are presented in Figure 2.…”
Section: Case Historymentioning
confidence: 99%
“…In humans, this immunotherapy is commonly used to treat cancer patients (6). In dogs, several studies on T-LAK have been conducted and demonstrated reinforcement of the recipient's immunity with this therapy (7,8).…”
Section: Introductionmentioning
confidence: 99%